Association of US State Implementation of Newborn Screening Policies for Critical Congenital Heart Disease With Early Infant Cardiac Deaths. Issue 5 (May 2018) - Abouk, Rahi; Grosse, Scott D.; Ailes, Elizabeth C.; Oster, Matthew E.
Abstract : (Abstracted from JAMA 2017;318(21):2111–2118) Timely detection of congenital heart disease in newborn infants, particularly before the patent ductus arteriosus closes in the first few days of life, can reduce the risk of a potentially fatal crisis occurring following discharge from the hospital. Critical congenital heart disease was added to the US Recommended Uniform Screening Panel for newborns in 2011, leading many US states to initiate policies requiring or recommending updated screening policies.